Responses to Concerning Posts on Social Media and Their Implications for Suicide Prevention Training for Military Veterans: Qualitative Study - Teo, Alan R; Strange, Wynn; Bui, Ricky; Dobscha, Steven K; Ono, Sarah S (JMIR Publications, 2020)
BackgroundA "concerning post" is a display of a user's emotional crisis on a social media platform. A better understanding of concerning posts is relevant to suicide prevention, but little is known about social media users' attitudes and responses to concerning posts. Military veterans in the United States are disproportionately affected by suicide, often use social media, and may have exposure to individuals with elevated suicide risk via concerning posts. ObjectiveThe objective of the study was (1) to obtain insight into whether and how US military veterans respond to members of their social network on social media (ie, "friends") who are experiencing substantial emotional distress, and (2) to identify potential interventions that could assist in users' response to concerning posts. MethodsWe recruited veterans through Facebook and conducted semistructured interviews with 30 participants between June and December 2017. We used a summary template for rapid analysis of each interview, followed by double-coding using a codebook based on topic domains from the interview guide. Members of the research team met regularly to discuss emerging patterns in the data, generate themes, and select representative quotes for inclusion in the manuscript. ResultsVeterans were reluctant to disclose emotional and health issues on Facebook, but they were open to reaching out to others' concerning posts. There was a complex calculus underlying whether and how veterans responded to a concerning post, which involved considering (1) physical proximity to the person posting, (2) relationship closeness, (3) existing responses to the post, and (4) ability to maintain contact with the person. Veterans desired additional training, backed by community-based veteran organizations, in how to respond to concerning posts from peers. ConclusionsThere is a need to incorporate features that will help veterans effectively respond to concerning posts from peers into suicide prevention training and to expand access for veterans to such training.